Application of Reciprocal Law in Returning Assets Resulting from Corruption - Wirawan, Helex; Ismet, Ismet (The journal of contemporary issues in business and government, 2021)
One of the unresolved legal issues in Indonesia is corruption. The problem of law enforcement is not yet optimal so that the assets resulting from criminal acts of corruption which are often more than national territory make it difficult to return. Mutual Legal Assistance in Criminal Matters, abbreviated as MLA, which is expected to help law enforcement is not yet optimal. Indonesia, as a participant country of the United Nations Convention Against Corruption (UNCAC), does not yet have a regulatory framework that comprehensively regulates the aspects recommended by the convention. This study aims to find out about efforts and mechanisms to optimize the role of MLA in the recovery of assets resulting from criminal acts of corruption in Indonesia, especially those abroad. This research is normative juridical research conducted by library research and interviews with informants related to the legislation and comparison approach. This article concludes that optimizing the role of MLA requires several steps such as implementing MLA in a more detailed technical format, optimizing the role of law enforcement as the implementer, and adopting the concept of Non-Conviction Based Asset Forfeiture (NCB).